Recent progress in bimetallic nanostructure impregnated metal-organic framework for photodegradation of organic pollutants - 김기현 (APPLIED MATERIALS TODAY, 2021)
Modern civilization has been accompanied by increased emissions of many harmful organic pollutants into ecosystems. Photocatalysis is a green, viable, and inexpensive technique to destruct harmful organic compounds into CO2 and water. In this regard, bimetallic nanostructure doped semiconductor (BDS) composites have gained a great deal of attention as photocatalysts with the aid of progress achieved in the design, synthesis, and modification of porous metal-organic frameworks (MOFs). In this review, the basic principle of BDS-based photocatalysis is discussed with a main emphasis on bimetallic nanostructure doped MOFs (BDM). The photocatalytic performances of various target species are thus evaluated for BDM in reference to other types of BDS or to its monometallic counterparts. Further, different synthesis approaches employed for their construction are also discussed. Moreover, the new challenges and future research prospects are highlighted to help gain advancement in the BDM-based photocatalytic systems. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bimetallic nanostructure; Metal-organic framework; Organic pollutants; Photocatalysis; Environmental remediation